Underestimated anuran radiations in the high andes: Five new species and a new genus of holoadeninae, and their phylogenetic relationships (anura: Craugastoridae) - De La Riva I. (2018)
Despite recent efforts to accelerate exploration and species description, the diversity of high Andean frogs remains highly underestimated. We report high levels of species diversity in direct-developing frogs or terraranas inhabiting the wet puna and adjacent cloud forests of the Amazonian versant of the Andes in Bolivia and Peru. Descriptive evidence of external morphology, distribution patterns and molecular phylogenetic analyses support the existence of nine unnamed species in two clades, which represents a 30% increase in species diversity for those clades. The relationships of these species and their relatives in Holoadeninae are tested using nuclear and mitochondrial genes for 159 terminals representing the 11 genera in this subfamily and 25 species of previously unknown relationships. Our results corroborate species monophyly in all but three cases and support the monophyly of all Holoadeninae genera, albeit the position of some differs between analyses. We propose a new genus (Microkayla gen. nov.) for the clade containing all Bolivian species formerly in Psychrophrynella plus five species from southern Peru. The new genus is monophyletic and supported by anatomical synapomorphies. Psychrophrynella is re-diagnosed and redefined to include three species from the Andes of southern Peru. We discuss the taxonomic instability associated with Noblella and Psychrophrynella due to the fact that the type species of both genera share a number of traits that support a close relationship. We also name and describe three new species of Bryophryne and two of Microkayla from Peru, provide baseline data for the future description of four Bolivian species of Microkayla, and describe the unknown mating calls of two species. Our results support that the grasslands of the Amazonian versant of the Andes harbour a large diversity of species with small altitudinal and horizontal distributions that replace each other along a latitudinal axis. These species belong to different lineages whose closest relatives are forest species, often from distant parts of the continent. These patterns suggest that high Andean environments were colonized several times independently by species with forest ancestors and which radiated into a multitude of species with remarkably similar ecomorphologies. The extent of these radiations remains obscured by a still rudimentary knowledge of species diversity due to insufficient fieldwork and taxonomic research. © 2017 The Linnean Society of London, Zoological Journal of the Linnean Society.